PSYCHOLOGICAL-PEDAGOGICAL CONDITIONS OF AIRCREW PROFESSIONAL TRAINING PROCESS OPTIMIZATION - Задкова, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article considers the conditions for designing the pedagogical technology of training future pilots to solve the problem situations arising in the professional activity in the process of basic training of the flight crew. These conditions comprise future pilots’ intellectual and creative development on the basis of modern technologies and teaching methods, attracting cadets to creative learning activity within the independent work, as well as widespread use of computer programs and simulators. The article highlights the fact that traditional methods and forms of aircrew professional training in relation to new aircraft operation fail to achieve optimum effect resulting in aviation accidents and air crashes.